(untitled) (Archive of Conferences, 2022)
Music pedagogy plays an important role in educating people artistically and aesthetically. Among them, traditional folk music has the ability to quickly affect a person, is easily accepted and form a person’s aesthetic attitude to the outside world. The article reflects the love for national music and values. Instead of folk music, special attention is paid